Model typowania sprawców zamachów z wykorzystaniem bojowych środków chemicznych - Daniel Kucharek (Przegląd Geopolityczny)
The purpose of this article is to try to identify the types of individuals and/or non-state organizations that are most capable of carrying out attacks on passenger aircraft using chemical warfare agents. The research was conducted on the basis of recorded cases in the past of deliberate use of chemical warfare agents in attacks not related to military activities. The first part of the article presents examples of attacks with the use of chemical warfare agents that were carried out by individuals or nonstate organizations. Using these examples, an attempt was made to create an ideological-psychological model of the perpetrators of the attacks, which can be used to select potential assassins with the use of chemical warfare agents. The research was conducted using characteristics of motivations and ideologies adhered to by individuals or non-state organizations.